Analisis pemetaan media tentang transaksi pembiayaan akad sharf di Indonesia dengan NVivo: Studi literatur review - Rohmadi; Doni Yusuf Bagaskara (Nur Science Institute, 2024)
This research aims to determine the media mapping analysis of Sharf Contract Financing Transactions in Indonesia using the NVivo tool. This research uses qualitative methodology with the help of NVivo and a literature review.